Penguatan Kapasitas Aparatur Desa di Medan Johor melalui Pelatihan Manajemen Informatika dan Tata Kelola SDM yang Akuntabel - Purnama Sari, Dian; Muhammad Syahrizal; Rizky Indra Saputra; Sari, Vina Winda; Peranginangin, Andreas P (Forum Kerjasama Pendidikan Tinggi, 2026)
This community service program aims to strengthen the capacity of village officials in Medan Johor District through training in informatics management and accountable human resource governance. The training was conducted using an interactive workshop and practice-based mentoring approach, focusing on digital information systems, administrative data management, and the implementation of public accountability principles in village governance. A total of 20 village officials participated in the program, and evaluations were carried out using structured pre- and post-training surveys. The results indicate a significant improvement in informatics skills (from an average score of 2.8 to 4.3), understanding of accountability (from 3.0 to 4.5), and work efficiency (from 2.9 to 4.2). Moreover, 92% of participants reported satisfaction with the program implementation. These findings demonstrate that the integration of digital training and public accountability ethics can effectively enhance local governance toward a more transparent, efficient, and participatory system. Nevertheless, limited training duration and digital infrastructure remain challenges for long-term implementation. This program serves as a model for digital-based capacity development of village officials in North Sumatra.